DNA Testing and Nafyu al-Nasab: A Comparative Study of Ali Jum'ah’s Fatwa and Its Socio-Legal Implications in Global Jurisdictions - Wawan Hermawan; Mohammad Rindu Fajar Islamy; Baidhillah Riyadhi; Kamaludin Kamaludin (UIN Sunan Gunung Djati, 2026)
This article analyzes the existence and juridical status of DNA testing in the determination (ithbāt) (establishment of lineage status) and negation (nafy) (denial, annulment, or rejection of lineage relationship) of lineage within the framework of Islamic family law through the perspective of the fatwas of Ali Jum’ah. The rapid development of forensic genetic technology has challenged the classical Fiqh framework, which traditionally recognizes liʿān (as the only legitimate mechanism for denying lineage). This study aims to reassess the relevance of Ali Jumʿah’s legal reasoning in the contemporary context by comparing legal approaches in Indonesia, selected Middle Eastern countries, and Western jurisdictions. This research employs a juridical-normative approach combined with comparative legal analysis and socio-legal perspectives. The study analyzes authoritative literature, fatwas of Islamic institutions, statutory regulations, and selected judicial decisions related to paternity determination and denial. The findings demonstrate that Middle Eastern legal systems generally recognize DNA evidence as qarīnah qawiyyah for verifying lineage but reject its use for nafyu al-nasab, consistent with Ali Jumʿah’s fatwa. Indonesia adopts a moderate approach, allowing DNA as corroborative evidence for determining biological relations but not as an independent basis for denying nasab in Islamic law. In contrast, Western legal systems treat DNA evidence as the primary determinant of paternity regardless of marital status. This study contributes to the development of an integrative framework for Islamic family law reform, proposing that DNA testing should function as strong corroborative evidence within a maqāṣid al-sharīʿah (Objectives of Shariah) framework that prioritizes the protection of lineage (ḥifẓ al-nasab), family stability, and the rights of the child.